Holding onto Hope in Times of Crisis: The Mediating Role of Hope in the Link Between Religious Motivation, Pandemic Burnout, and Future Anxiety Among Turkish Older Adults - Muhammet Enes Vural; Harun Geçer; Hızır Hacıkeleşoğlu; Murat Yıldırım (Religions, 2025)
The COVID-19 pandemic has not only triggered a global health crisis but also profoundly disrupted the psychological well-being of older adults, leading to heightened levels of burnout, uncertainty, and anxiety about the future. During times of crisis, intrinsic religious motivation may offer a spiritual grounding that fosters hope, a critical internal resource in sustaining emotional balance. This study investigates the mediating role of hope in the relationship between intrinsic religious motivation, pandemic-related burnout, and future anxiety among Turkish older adults. A total of 427 participants (Mage = 66.98, SD = 7.23) were recruited using a cross-sectional design. Participants completed validated measures of intrinsic religiosity, dispositional hope, pandemic burnout, and future anxiety. Structural equation modeling revealed that intrinsic religious motivation positively predicted hope and negatively predicted both burnout and future anxiety. Moreover, hope significantly mediated the relationship between intrinsic religious motivation and both outcome variables. These findings suggest that religious meaning-making may enhance psychological resilience by promoting hope, thereby mitigating the mental health burden during large-scale crises. The study enhances understanding of culturally embedded support mechanisms and highlights the role of faith-based inner resources, such as intrinsic religious motivation and hope, in fostering resilience among older adults during uncertainty and crisis.